Conceptualizing Buddhisization: Malaysian Chinese Buddhists in Contemporary Malaysia - Tan, Lee Ooi (Religions, 2022)
This article conceptualizes the term "Buddhisization" to understand religious manifestations of Buddhist communities in contemporary Malaysia. By Buddhisization, I refer to a process of influencing or being influenced to be a Buddhist. The purpose of this conceptualization, apart from basic description and definition, is to outline some contexts for the use of Buddhisization and rationale behind the process. Drawing on in-depth interviews with Malaysian Chinese Buddhists, this study proposes six aspects of Buddhisization from the common experiences of Malaysian Chinese Buddhists. These aspects are the formalization of the taking refuge ceremony, participation in Buddhist associations, Buddhist examination, popularization of meditation courses, Buddhist weddings and Buddhist funerals. From experiences in Malaysia, this article suggests that the Buddhist minority context has enabled the process of being Buddhist at individual and institutional levels through initiatives and efforts of the Buddhist community. Urban educated middle-class Chinese Buddhists are inclined towards an acceptance of Buddhisization. As a consequence, it has complicated the journey of nation building in multi-religiosity Malaysia.